2014
DOI: 10.1016/j.jss.2013.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Increased estrogen receptor alpha in experimental aortic aneurysms in females compared with males

Abstract: INTRODUCTION Estrogen receptor alpha (ERα) has been identified in the vessel wall, offering vasoprotective effects when upregulated. Estrogens are known to mediate the inflammatory mileu, and inflammation has long been associated with abdominal aortic aneurysm (AAA) formation. Therefore it is theorized that increased estrogen receptor in females contributes to their relative resistance to AAAs. The study’s objective was determining gender differences in ERα levels during experimental AAA formation. METHODS I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…68 Increased levels of Serpine1 decrease MMPs by reducing plasmin in the blood and can modulate plasminogen-mediated apoptosis of vascular SMCs. 68 Laser et al 37 showed an increase of aortic wall Esr1 in female compared with male mice aortas, which was inversely correlated with MMP activity, suggesting a protective role of Esr1 during AAA formation likely because of a decreased inflammation. Another study concluded that genetic susceptibility is important in AAA development, as significantly more macrophages were found in C57BL/6 male than female mice, but there was no difference between sexes in B6129 mice.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 97%
See 1 more Smart Citation
“…68 Increased levels of Serpine1 decrease MMPs by reducing plasmin in the blood and can modulate plasminogen-mediated apoptosis of vascular SMCs. 68 Laser et al 37 showed an increase of aortic wall Esr1 in female compared with male mice aortas, which was inversely correlated with MMP activity, suggesting a protective role of Esr1 during AAA formation likely because of a decreased inflammation. Another study concluded that genetic susceptibility is important in AAA development, as significantly more macrophages were found in C57BL/6 male than female mice, but there was no difference between sexes in B6129 mice.…”
Section: Sex Differences In Aaa Animal Models the Role Of Endogenous mentioning
confidence: 97%
“…36 Interestingly, women with AAAs >5.5 cm had lower levels of MMP9 compared with women with AAA <5.5 cm, which could be explained either by MMP9 degradation in the aneurysmal wall or a reduction in the MMP9 production as the aneurysm grows. 36 Laser et al 37 found that ESR1 protein levels were 80% higher in the aortic wall of women than in men with AAA. Furthermore, aromatase, an essential enzyme of estrogen synthesis, was expressed in aortic cells expressing smooth muscle markers (SMaA) and macrophage markers (CD68 and Mac-2) in human AAA tissues.…”
Section: Role Of Sex Hormones In Aaa Development and Growthmentioning
confidence: 99%
“…Results demonstrate that aortas from elastase-perfused female rats and mice have lower MMP activity than males [33,47]. Likewise, ovariectomy of female Wistar rats increased aortic MMP-2 and -9 activity [39].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 88%
“…Deletion of aromatase abolished the protective efects of female gender on elastase-induced AAAs [53]. Aortas from female mice had higher expression levels of ER α compared to male mice by day 3 of elastase perfusion [47]. Increased ERα expression was also detected in female human AAA patients compared to males [47].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 96%
See 1 more Smart Citation